Low-loss gears precision planetary gearboxes: reduction of the load dependent power losses and efficiency estimation through a hybrid analytical-numerical optimization tool - Concli, F. (Forschung im Ingenieurwesen, 2017)
In the field of robotics, extremely accurate gearboxes are mandatory in order to ensure the adequate precision required by the automatic processes. For these applications, planetary gearboxes represent one of the most attractive solutions because they ensure high reduction ratios in a compact solution. However, their compactness and high power density, imply some thermal limitations. In order to overcome this problem, new gear designs have been studied by a hybrid analytical-numerical approach in order to reduce the power dissipation and, consequently, the operating temperatures. The efficiency increase is obtained mainly by a reduction of the module of the gears. This, together with other modifications of the tooth form (pressure angle, profile shift, etc.), allows to reduce the relative sliding between the tooth flanks that causes the power loss maintaining at the same time an adequate load carrying capacity. Low-loss gears have already been studied by other authors on bigger gears. Furthermore, by means of dedicated CFD simulations performed with an especially developed tool based on the open-source code OpenFOAM®, it has been shown that the sliding optimized design has a positive impact also on the churning power losses. The global winning in terms of reduction of the gear meshing power losses can be assessed in about 50%, depending on the reduction ratio. The new design has been validated by means of experimental tests performed in the internal laboratory of the company. The results have fully validated both the numerical approach and the new design.